2014
DOI: 10.1007/s00246-014-0901-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-10a and MiR-10b Target the 3′-Untranslated Region of TBX5 to Repress Its Expression

Abstract: As a well-known transcription factor, TBX5 is involved in embryonic cardiac development. Although TBX5 functions in a dose-dependent manner, the posttranscriptional regulation of human TBX5 is poorly understood. Thus, this study aimed to identify microRNAs that modulate TBX5 expression. Luciferase assays were used to screen miRNAs predicted to modulate TBX5 expression. Using quantitative reverse transcriptase-polymerase chain reaction and Western blot analysis, the authors found that miR-10a and miR-10b signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Rather than acting independently of one another, these systems act in an integrated fashion to regulate cardiac gene expression in a coordinated manner. In fact, several cardiac-expressed miRNAs were found to be involved in the TBX5 [114,121], GATA-4 [122][123][124][125][126], SRF/MYOCD [124,126,127], and PITX2 [97] regulatory network in settings of cardiovascular disease. There is evidence that circulating miRNAs may be used as biomarkers for patients with HFpEF, but their expression has not yet been assessed in the diastolic heart [128].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than acting independently of one another, these systems act in an integrated fashion to regulate cardiac gene expression in a coordinated manner. In fact, several cardiac-expressed miRNAs were found to be involved in the TBX5 [114,121], GATA-4 [122][123][124][125][126], SRF/MYOCD [124,126,127], and PITX2 [97] regulatory network in settings of cardiovascular disease. There is evidence that circulating miRNAs may be used as biomarkers for patients with HFpEF, but their expression has not yet been assessed in the diastolic heart [128].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the average levels of miR-10a and miR-10b in heart tissue of CHD (n=28) were as approximately 3-fold high as those in controls (n=9). [27] However, the subtypes of heart defects were not specified in this study. A stratification analysis on the expression levels of miR-10a and miR-10b in terms of the subtypes of heart defects would be of more pathobiological signifi cance.…”
Section: Authorsmentioning
confidence: 95%
“…Wang et al [27] 28 CHD samples (4 atrium, 3 ventricle, 1 auricle, 2 ventricular septum, 10 outlet, and 8 aorta samples) versus 9 normal heart tissue samples qRT-PCR miR-10a, miR-10b…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, levels of norepinephrine found altered in symptomatic patients, especially those with unrepaired congenital heart disease, Eisenmenger syndrome, pulmonary hypertension and adult congenital heart failure [38]. These are used as, molecular markers for prediction of congenital heart disease [39]. Similarly, level ofTBX5 a transcription factor diagnose embryonic cardiac defects [40].…”
Section: Molecular Markersmentioning
confidence: 99%